Individual Characteristics, Multicultural Experiences And Acceptance Of Diversity Among Postgraduate Students In Selected Malaysian Public Universities - Ramezanpour, Shiva (2019)
Much research exists on the effect of intercultural interaction and diversity engagement on the internationalization of higher education and students’ growth. However, not much exists on how differences in the multicultural experiences (in forms of students’ engagement, participation in events and interaction with other students of different cultures and nationality) of local and international postgraduate students can influence their acceptance of diversity. Even less exists on the interaction effect of individual characteristics of local and international students on the relationship of their multicultural experiences and acceptance of diversity especially in the context of Malaysia.